Theoretical Study of a Design Method for Underexcavation in Building Rectification - Jun-Hua Xiao; Jian-Ping Sun; Xin Zhang; Zong-Bao Jiang; Dao-Tong Guo (Advances in Civil Engineering)
For buildings with shallow foundations embedded in natural soil sediments, the underexcavation method is often used to correct building inclination. Relying on engineering experience and close field monitoring, rectification has been conducted successfully. However, theoretical studies are relatively scarce, resulting in an inadequately informed rectification design and procedure. Assuming the soil is an ideal elastic-plastic body, a simplified analysis was adopted to study the issue theoretically. First, the redistribution of the base contact pressure after building inclination was deduced. Second, according to the force balance between the total contact pressure of the base and the total stress on the horizontal plane at the excavation hole, the limit hole spacing at the critical state of building back tilt was obtained, which was also the preferable hole spacing for soil strip collapse. Third, because the amount of anticipated forced settlement at a certain section of soil excavation is equal to the volume of soil hole collapse, an accurate formula for the hole diameter was obtained. Combined with engineering experience, suggestions for the design procedure were proposed. Finally, two case histories were introduced to verify the correctness and practicability of the theoretical formula for hole spacing and diameter. These two key parameters provide a strong theoretical basis for building rectification in future engineering practice.